Noise and vibration control for building services systems : CIBSE guide B4 : 2016. (Chartered Institution of Building Services Engineers, 2016)
This document, which forms chapter 4 of CIBSE Guide B, provides guidance to building services engineers and others involved in the design of building services on the generation, prediction, assessment and control of noise and vibration from building services, so that designers may produce systems which meet acceptable noise limits. Noise reduction procedures are always much more effective and economic when introduced at the design stage than when applied retrospectively. Therefore it is important that the issue of noise is taken into account at an early stage of the design process, involving advice from an acoustics expert in particularly noise sensitive situations. The aim of this chapter is to provide guidance to enable building services systems to be designed to achieve acceptable levels of noise in addition to meeting requirements relating to aerodynamics, energy usage and economics.